Online Savings Intention of Individual Customers: The Moderate Role of Mental Accounting - Uong, Lan Ngoc Thi (Journal of Posthumanism, 2025)
Based on the extended theory of planned behavior, this study aims to explore the factors influencing individual customers’ online savings intentions and evaluate the moderating role of mental accounting. A quantitative research method is employed through a linear regression model using the hierarchical approach. The analysis of 310 samples reveals that attitudes, subjective norms, perceived behavioral control, financial benefits, the safety of savings deposits, and the bank's image positively impact individual customers’ intention to save online. Additionally, mental accounting positively moderates the relationship among financial benefits, perceived behavioral control, and the safety of savings deposits regarding online savings intentions, while negatively affecting the relationship between subjective norms and online savings intentions. Furthermore, mental accounting was found to have no moderate role in influencing the relationship between a bank's image and individual customers' online savings intentions. The findings of this study provide a foundation for implications aimed at promoting modern, safe, and sustainable saving habits in the digital economy of an emerging market like Vietnam.